Research on plastic material / Razaini Hassan and Mohd Fuad Idris - Hassan, Razaini; Idris, Mohd Fuad (Faculty of Mechanical Engineering, 1992)
As we know, plastics are the watchword of our everyday environment. Plastics have gained in application and acceptance. In many of industries their inclusion has provided a significant improvement in the performance characteristics of the product. By the way, before we discuss further about plastics, it is perhaps vital to have a clear understanding of the basic principles of polymer science. This because the terms “polymer” and “plastic” are often used as if they are synonymous. But in fact they are not.